2017
DOI: 10.3791/55147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Diagnostics in Revision Arthroplasty: Implant Sonication and Multiplex Polymerase Chain Reaction

Abstract: In orthopedic patients, foreign body-associated infections, especially periprosthetic joint infections (PJIs), are a devastating complication of arthroplasty. Infection requires complex treatment, may result in long hospitalization and causes considerable costs. Multiple surgical revisions can be necessary in these patients, with a loss in function as well as in quality of life.The routine preoperative diagnostics include blood examination for C-reactive protein (CRP) and other biomarkers, as well as joint asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Renz et al 23 combined the mPCR with the sonication of synovial fluid and found a sensitivity of 51% and a specificity of 94% respectively. Similar results were found by Hischebeth et al 24 presenting a sensitivity of 66.7% and a specificity of 100%. In their study mPCR and fluid sonication were also investigated together.…”
Section: Discussionsupporting
confidence: 89%
“…Renz et al 23 combined the mPCR with the sonication of synovial fluid and found a sensitivity of 51% and a specificity of 94% respectively. Similar results were found by Hischebeth et al 24 presenting a sensitivity of 66.7% and a specificity of 100%. In their study mPCR and fluid sonication were also investigated together.…”
Section: Discussionsupporting
confidence: 89%
“…However, these biomarkers only identify the presence or absence of infection, and do not specify the particular offending organism or its antibiotic sensitivities. Some diagnostic techniques which may improve the ability to detect organisms, which are difficult to isolate or culture and potentially provide information on antibiotic resistance genes, include PCR, next‐generation sequencing and prosthesis sonication . While some preliminary data exists on all of these techniques, there is concern regarding the fact that the increased sensitivity may come at the cost of a higher false‐positive rate, and focused research is needed in this area.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, the authors suggested that if implant sonication is feasible in a particular clinic, it should be included in the diagnosis workflow as it has superior ability to recover the infecting organism. Alternatively, sonicate fluid can be analyzed using multiplex PCR methods in order to determine the infecting organisms without the need for culture 103 . The addition of molecular diagnosis by PCR may improve the accuracy of sonicate fluid because it has the ability to identify viable and nonviable bacteria as well as decreasing the overall time to diagnose from days to hours 104 .…”
Section: New Advancements In Diagnosis Of Pjimentioning
confidence: 99%
“…Alternatively, sonicate fluid can be analyzed using multiplex PCR methods in order to determine the infecting organisms without the need for culture. 103 The addition of molecular diagnosis by PCR may improve the accuracy of sonicate fluid because it has the ability to identify viable and nonviable bacteria as well as decreasing the overall time to diagnose from days to hours. 104 Ultimately, future studies are warranted to achieve consensus on the use of sonication in the clinic.…”
Section: Implant-based Markers For Pji Diagnosismentioning
confidence: 99%